Functional Peculiarities of Cumulative Negation in Literary Language (Proceedings of Southern Federal University. Philology, 2015)
Serebryakova S.V., Serebryakov A.A. (North-Caucasus Federal University, Stavropol, Russian Federation)The article «Functional Peculiarities of Cumulative Negation in Literary Language» deals with the pragmatic potential of the cumulative negation as the stylistically specified concentration of statements of negative semantics. The latter provides statements expressiveness and realizes implicitly and explicitly the pragmatic meaning of the negative judgment. The material for the article has been the short stories by modern German writer Judith Hermann with the emphasis on the narrative «Nichts als Gespenster» which style is mainly characterized by psycologism. The language means and techniques give the insight into character’s inner world. The cumulative negation is understood as the pragmatically relevant concentration of statements with negative semantics having varied structure and conceptual significance. The negative-evaluative modus of the main character’s worldview is realized through different language and contextual negation forms: linguistic and paralinguistic, explicit and implicit, neutral and expressive, recurrent and parallel, single and multiple. Despite the weak reference, little informativeness and static character, the negative structures serve to developing the main topic of the narrative, i.e. the inner discomfort, being unsure in her feelings reciprocality and the vagueness of the main character’s future. The retrospective vector of the cumulative negation marks fragmentary, evaluationally controversial reminiscences of the main character about her three-months visit to America, and it also provides the text coherence and text-forming function.Key words: cumulative negation, pragmatic potential, expressiveness, judgment, literary text, psychologism, negative semantics, communicative situation.DOI: 10.18522/1995-0640-2015-4-99-106